Armenian Energy System Development: The Prospects of EAEU Single Energy Market - Sokolova, Elizaveta S.; Panina, Olga V.; Krasyukova, Natalia L.; Kushchev, Nikolay P. (International Journal of Energy Economics and Policy, 2022)
Armenia today is a country with significant energy and economic issues. The country has come over a difficult period of military conflict, it’s highly dependent on imports of energy resources, the national energy system is out-of-date. The energy issues require significant financial investments, which can’t be provided in the current conditions. This defines the theoretical and practical significance of the research, especially in the context of the need for reforms in energy sector and in economy in general. In addition to that Armenia is isolated from EAEU single energy market, which proves to be a problem for the country. The authors focused on the analysis of weak and strong points of the Armenian energy industry, revealing and proving, that the current situation harms economic development of the country. The key strong points revealed are the willingness of cooperation with Russia, readiness for the green transformation, access to the international financial market, readiness of the legal framework. Based on these findings and on the econometric model, that proves that natural gas, oil and hydroenergy are the most significant energy resources for the GDP of the country, contributing to its growth, the authors have developed recommendations for the development of the Armenian energy industry, taking into account the poor situation with financial resources in the country in general and the dependency of Armenian energy system on the Russian energy sector companies.